Management of congenital missing maxillary incisors by orthodontic treatment followed by fixed prosthesis (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Fixed prosthetic restoration has become a primary treatment option for the replacement of congenitally missing lateral incisors where adequate Implant restorations have limited use due to many factors. The central incisor and canine often erupt less than optimal positions adjacent to the edentulous lateral incisor space, and therefore preprosthetic orthodontic treatment is frequently required. Derotation of the central incisor and canine, space opening and correction of root proximities may be required to create appropriate space, in which fixed prosthesis may achieve an esthetic restoration. This paper presents two case reports with congenital missing lateral incisors and one case report with missing central incisors due to trauma. The paper also discusses the aspects of preprosthetic orthodontic diagnosis and the treatment that needs to be considered with conservative and fixed prosthetic replacement . DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.15998 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 16-19